The current genomic approaches for common respiratory diseases - Lin,S; Zhang,M; Zhang,Y (Journal of Investigative Genomics, 2016)
Common respiratory diseases including asthma, chronic obstructive pulmonary disease (COPD) and lung cancer are increasing worldwide. Genomic approaches for the diseases provided new insights of the mechanisms and revealed the new therapeutic targets. Genome-wide association studies (GWAS), epigenetic studies, transcriptional profiling, RNA sequencing, chromatin immune precipitation (ChIP) sequencing and microbiota investigation make personalized medicine for common respiratory diseases possible in the near future. In this review, we summarize the current progress of genomic approaches for asthma, COPD and lung cancer and also discuss the future directions of the research of the diseases.